Hi guys,

I am having trouble with what should be an easy problem:

Given:

s_k = q_k + 2*q_(k-1) - q_(k-2)

q_k= 2*b_k - 1

b_k= a_k (xor) b_(k-2)

Find a simplified expression for a_k in terms of s_k if it is known that

a_k = [b_k + 2* b_(k-1) - b_(k-2) ] _mod2

-----------

I only have gotten to the point where I set b_k= (q_k+1)/2 and used that logic for the (k-nth) terms, but its still lengthy, and I just have a feeling that that is not the answer.

Any help would be appreciated, thank you.